The influence of the pack decarburizing process with Pinctada maxima shell powder agent on the properties of high carbon steel - Darmo, Sujita; Soenoko, Rudy; Siswanto, Eko; Widodo, Teguh Dwi (Eastern-European Journal of Enterprise Technologies, 2019)
In the present study, ductility enhancement of high carbon steel AISI 420 was conducted by pack decarburizing method to improve mechanical properties of this steel. This specimen was placed in a rectangular box containing pinctada maxima shell powder (PMSP) mixed with the carburizing agent with different percentage variations and heat treated in an oxygen atmosphere at different temperatures and soaking times. Phase analysis results indicated that the pack decarburizing process at a temperature of 900 °C, for soaking time 3 hours and an additional 30 % PMSP in the carburizing agent causing the martensit microstructure, the surface hardness number and thickness of carbon layer decreased but the impact energy of high carbon steel AISI 420 increased. The surface hardness number, carbon layer thickness each respectively decreased by 63 % and 60 %, but impact energy or impact strength increased by 33 %. This phenomenon indicates that the pack decarburizing treatment causes carbon diffusion from the surface of the specimens to the carburizing agent or reverse carbon diffusion occurs, because the concentration of carbon in the carburizing agent is higher than the surface of the specimen. The addition of PMSP in the carburizing agent increases the occurrence of carbon diffusion from the surface of specimens to the carburizing agent or reverse carbon diffusion occurs, because differences in concentration and influence of PMSP contains elements of Ca which function as catalysts or energizers. The results showthat the pack decarburizing process with an additional PMSP in the carburizing agent accelerates the diffusion of carbon atoms out the surface of the specimens (reverse carbon diffusion process), thus decreasing the thickness of the surface carbon layer, surface hardness number and increasing the impact energy